Exploring the Practice of Norm-Referenced and Criterion-Referenced Assessment in Islamic Education - Azizah Putri Irmayanti; Remiswal Remiswal; Khadijah Khadijah; Syamsi Syamsi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Exploring the Practice of Norm-Referenced and Criterion-Referenced Assessment in Islamic EducationObjective: This study aims to reveal and analyze the application of Norm-Referenced Assessment (NRA) and Criterion-Referenced Assessment (CRA) in Islamic education. Methods: This research uses descriptive qualitative methods, data collection using observation, interviews, and documentation studies. Data analysis uses reduction, presentation, and conclusion techniques. Results: Islamic education teachers at SMPN 24 Padang have applied norm-referenced assessment in the learning process and criterion-referenced assessment in certain aspects, such as attitude and skills assessment. Conclusion: While both can improve academic understanding, there is still a need to integrate these two assessment methods with a more holistic approach that measures cognitive ability and develops students' Islamic character. Contribution: The research improves the quality of Islamic education learning assessment according to the demands of the applicable curriculum.INDONESIAN: Mengungkap Praktik Penilaian Acuan Norma dan Penilaian Acuan Kriteria dalam Pembelajaran Pendidikan Agama IslamTujuan: Penelitian ini bertujuan untuk mengungkap dan menganalisis penerapan Norm-Referenced Assessment (NRA) dan Criterion-Referenced Assessment (CRA) dalam konteks pendidikan Islam. Metode: Penelitian ini menggunakan metode kualitatif deskriptif, pengumpulan data menggunakan observasi, wawancara dan studi dokumentasi. Analisis data menggunakan teknik reduksi, penyajian dan penarikan kesimpulan. Hasil: Guru pendidikan agama islam di SMPN 24 Padang tlah menerapkan penilaian acuan norma dalam proses pembelajaran dan menerapkan penilaian acuan kriteria pada aspek tertentu seperti penilaian sikap dan keterampilan. Kesimpulan: Meskipun keduanya dapat meningkatkan pemahaman akademis, namun masih ada kebutuhan untuk mengintegrasikan kedua metode penilaian ini dengan pendekatan yang lebih holistik, yang tidak hanya mengukur kemampuan kognitif, tetapi juga mengembangkan karakter Islam siswa. Kontribusi: Penelitian berkontribusi sebagai bahan pertimbangan dalam upaya meningkatkan kualitas penilaian pembelajaran pendidikan agama islam sesuai dengan tuntutan kurikulum yang berlaku.